2018
DOI: 10.3390/pharmaceutics10030095
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Drug Nanocomposites Prepared by the Aerosol Solvent Extraction System for Enhancing Drug Solubility and Stability

Abstract: Ginsenosides are the pharmacologically active constituents of ginseng. So far, more than 30 ginsenosides have been identified and widely used in pharmaceutical formulations. However, the therapeutic applications of ginsenosides are hampered by their poor solubility and low bioavailability. In this study, we selected two of the most important ginsenosides-Re and Rh2 as model drugs to prepare ginsenoside drug nanocomposites (NanoGS) using the simple aerosol solvent extraction system (ASES) technique to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It can be demonstrated that the inclusion of GR in the scaffold will not affect the main phase structure of MSCS. Compared to G0, G5 had a high crystallinity sharp peak showing at 2θ = 41°, which can represent the fact that the scaffold contains ginsenoside [ 30 ]. The functional groups of the synthesized GR-loaded MSCS were analyzed using FTIR spectrophotometry as shown in Figure 2 B.…”
Section: Resultsmentioning
confidence: 99%
“…It can be demonstrated that the inclusion of GR in the scaffold will not affect the main phase structure of MSCS. Compared to G0, G5 had a high crystallinity sharp peak showing at 2θ = 41°, which can represent the fact that the scaffold contains ginsenoside [ 30 ]. The functional groups of the synthesized GR-loaded MSCS were analyzed using FTIR spectrophotometry as shown in Figure 2 B.…”
Section: Resultsmentioning
confidence: 99%
“…Aerosol solvent extraction system (ASES) means that supercritical fluid CO 2 and solution are pumped into a previously installed precipitation reactor through a nozzle, in which the solute is oversaturated and precipitated into nanoparticles through the extraction and absorption of CO 2 to the solvent and the diffusion of solvent molecules to CO 2 ( Yu et al, 2006 ). Tao et al (2018) synthesized minor ginsenoside Rh2 and re-drug nanocomposites using ASES technology. The author chose vapor-over-liquid, subcritical liquid and supercritical liquid to prepare.…”
Section: Preparation Of Minor Ginsenoside Nanoparticlesmentioning
confidence: 99%
“…Furthermore, an effective ginsenosides DDS was fabricated with an aerosol solvent extraction system using ginsenosides Re and Rh2 as drug models. Remarkably, nanocomposites (NanoGS) exhibited a higher dissolution rate and significant cytotoxicity to the MCF-7 cancer cells than did the ginsenosides in vitro [ 21 ]. It has been verified that ginsenoside Rg3 modified with amino acids, peptides and CS can pass through the blood brain barrier (BBB) and prolong the blood circulation time of drugs in vivo.…”
Section: Ginsenosides As Bifunctional Drugs and Nanocarriers In Ddssmentioning
confidence: 99%
“…Ginsenosides have been proved to exhibit good anticancer activity and targeting ability, both as a drug and as an excipient compound simultaneously [ 16 20 ]. However, due to their poor water solubility caused by the lipophilic steroid skeleton, GI instability [ 21 ], low oral absorption rate, short half-life, rapid clearance and other pharmacokinetic properties [ 22 ], most ginsenosides have a bioavailability of < 5% [ 23 ]. In addition, non-targeted aggregation can induce adverse reactions such as nerve, liver, and kidney toxicity, thus limiting clinical application [ 24 ].…”
Section: Introductionmentioning
confidence: 99%